Relationship Between Erectile Dysfunction, Diabetes and Dyslipidemia in Hypertensive-Treated Men - Zamorano-Leon, Jose J; Segura, Antonio; Lahera, Vicente; Rodriguez-Pardo, Jose M; Prieto, Rafael; Puigvert, Ana; Lopez-Farre, Antonio J. (Urology Journal, 2018)
Purpose: PRESIDEN study is a large study to analyze the erectile dysfunction (ED) incidence in Spanish population. The present study is a pilot sub-analysis from PRESIDEN to determine if ED or plasma testosterone (TST) level in controlled hypertensive patients may be associated with comorbidities and/or plasma nitrite+nitrate and antioxidant capacity. Materials and Methods: Forty-four hypertensive individuals were aleatory selected from PRESIDEN study, matching by age (28 showing ED and 16 without ED). Result: Diabetes was present in 28.57% of ED patients and in 18.75% of patients without ED. In patients with and without ED, increasing age showed tendency of higher frequency of an additional comorbidity (diabetes or dyslipemia) (P = .09). Apparently, plasma TST levels were lower in older ED patients compared to younger patients with and without ED, although it did not reach statistical significance (P = .69). Older ED patients also showed lower TST levels than older patients without ED, although it was not statistical significant (16.15 ± 2.84 vs 13.91 ± 2.77; P = .69). Dyslipidemia was showed by 52.17% with lower TST (? nmol/L) while 23.80% of patients with plasma TST levels > 15 nmol/L had dyslipidemia. The percentage of ED patients was similar between patients with low and high TST levels. Conclusion: More ED hypertensive patients seem to show two comorbidities (diabetes and dyslipidemia) than hypertensive patients without ED. Younger patients with ED tended to show more commonly diabetes than older ED patients. Plasma TST levels were not associated with more prevalence of ED but lower plasma TST levels showed tendency to higher prevalence of dyslipidemia.